Role of time from transplantation to biopsy in histologic ABMR: A single center report. Issue 12 (1st November 2022) - Chancay, Jorge; Liu, Caroline; Chauhan, Kinsuk; Andersen, Lisa; Harris, Cynthia; Coca, Steven; Delaney, Veronica; Tedla, Fasika; De Boccardo, Graciela; Sehgal, Vinita; Moledina, Dennis; Formica, Richard; et al.
Abstract: Background: Allograft biopsies with lesions of Antibody‐Mediated Rejection (ABMR) with Microvascular Inflammation (MVI) have shown heterogeneous etiologies and outcomes. Methods: To examine factors associated with outcomes in biopsies that meet histologic ABMR criteria, we retrospectively evaluated for‐cause biopsies at our center between 2011 and 2017. We included biopsies that met the diagnosis of ABMR by histology, along with simultaneous evaluation for anti‐Human Leukocyte Antigen (HLA) donor‐specific antibodies (DSA). We evaluated death‐censored graft loss (DCGL) and used a principal component analysis (PCA) approach to identify key predictors of outcomes. Results: Out of the histologic ABMR cohort ( n  = 118), 70 were DSA‐positive ABMR, while 48 had no DSA. DSA(+)ABMR were younger and more often female recipients. DSA(+)ABMR occurred significantly later post‐transplant than DSA(‐)ABMR suggesting time‐dependence. DSA(+)ABMR had higher inflammatory scores (i, t), chronicity scores (ci, ct) and tended to have higher MVI scores. Immunodominance of DQ‐DSA in DSA(+)ABMR was associated with higher i+t scores. Clinical/histologic factors significantly associated with DCGL after biopsy were inputted into the PCA. Principal component‐1 (PC‐1), which contributed 34.8% of the variance, significantly correlated with time from transplantation to biopsy, ci/ct scores and DCGL. In the PCA analyses, i, t scores, DQ‐DSA, and creatinine at biopsy retained significant correlations with GL‐associated PCs. Conclusions: Time from transplantation to biopsy plays a major role in the prognosis of biopsies with histologic ABMR and MVI, likely due to ongoing chronic allograft injury over time.